Cell Membrane Remodeling Mediates Polymyxin B Resistance in Klebsiella pneumoniae: An Integrated Proteomics and Metabolomics Study - Chen, Xinyi; Tian, Jingjing; Luo, Can; Wang, Xiaofan; Li, Xianping; Wang, Min (Frontiers in Microbiology, 2022)
Polymyxin B (PB) is introduced into the clinic as the last-line therapy against carbapenem-resistant Klebsiella pneumoniae (CRKP). Unfortunately, increased resistance to PB in Klebsiella pneumoniae (K. pneumoniae) has threatened global health. Resistance of K. pneumoniae to PB was induced by passaging in serial concentrations of PB and determined by microbroth dilution method. Growth characteristics of induced strains including growth curve, reversibility of resistance and biofilm formation (crystal violet staining method) were measured. This study employed TMT-labeled quantitative proteomics and LC-MS/MS metabolomics analysis to investigate the key biological processes associated with PB resistance in K. pneumoniae. A total of 315 differentially expressed proteins (DEPs) were identified, of which 133 were upregulated, and 182 were downregulated in the PB resistant K. pneumoniae. KEGG enrichment analysis revealed that the DEPs were mainly involved in ATP-binding cassette (ABC) transporters and cationic antimicrobial peptide (CAMP) resistance. Proteins related to central carbon metabolism were inhibited in the PB resistant K. pneumoniae, but proteins mediating LPS modification were activated. Transcriptional levels of CAMP resistance-related proteins were significantly different between PB susceptible and -resistant K. pneumoniae. PB treatment led to an increase in reactive oxygen species (ROS) levels of K. pneumoniae. Metabolomics data demonstrated that 23 metabolites were significantly upregulated in PB resistant K. pneumoniae, 5 were downregulated. The differential metabolites were mainly lipids, including glycerophospholipids, sphingolipids and fatty acids. Exposure to PB resulted in increased level of phospholipid transport gene mlaF in K. pneumoniae. Our study suggested that membrane remodeling and inhibited central carbon metabolism are conducive to the development of PB resistance in K. pneumoniae.